Standardization of the traditional Pudam process in the manufacturing of Siddha medicine Anna Pavala Chendooram by using an innovative electrical device - A.S. Ganesh Kumar; Senthilvelan Selvaraj; V.M. Ravichandran; P Selva Shunmugam; V. Kamalanathan (Journal of Ayurveda and Integrative Medicine, 2025)
Background: The Siddha medicine system is one of the oldest traditional medicine systems and requires engineering equipment to reduce skill dependency for medicine manufacturing without compromising the efficacy of the medicine. Objective: The objective of the current work was to study the standard manufacturing method for a Siddha medicine anna pavala chendooram as per the conventional method and manufacture it in an electrical device designed for pudam process characterize it. Material and methods: Annabedhi (Ferrous sulfate) and kodipavalam (Coral) were taken as raw materials, anna pavala chendooram was prepared in the pit per conventional methods, and the same medicine was prepared in an electrical device for pudam; the prepared medicine from the pit and the device were characterized using modern scientific methods. Results: The maximum pressure built inside the sealed agal during the pudam was 35 mbar, and the maximum temperature during the pudam captured was 635 °C at the bottom. The XRD analysis reveals that the raw material consists of Fe2O3 (H2O)4, 2Fe (OH) SO4, and CaSO4 (H2O)4, and the finished medicine consists of Fe2O3 and CaSO4. The XRF analysis reveals that the major oxides in finished medicines were Fe2O3(T), SO3, CaO, and MgO. The average particle size of finished medicine from the pit is 6.52 μm, and the finished medicine from the device with seelaimann is 6.45 μm, and from the device without seelaimann is 6.28 μm. Conclusion: The pudam process for making anna pavala chendooram can be done using the device for pudam with the temperature profile obtained from the pit.